2015
DOI: 10.1002/bjs.9782
|View full text |Cite
|
Sign up to set email alerts
|

Meta-analysis of reconstruction techniques after low anterior resection for rectal cancer

Abstract: Colonic J pouch and side-to-end CAA or transverse coloplasty lead to a better functional outcome than straight CAA for the first year after surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
72
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 102 publications
(76 citation statements)
references
References 34 publications
2
72
1
1
Order By: Relevance
“…The present trial failed to demonstrate any benefit of a J pouch in reducing the rate of AL, and was unable to confirm the findings of studies that foresaw a significant advantage of CJP over the traditional SCRA technique. Differences in primary endpoint, study design, definition of selection criteria and method of diagnosis of AL might explain discrepancies between the present results and those of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…The present trial failed to demonstrate any benefit of a J pouch in reducing the rate of AL, and was unable to confirm the findings of studies that foresaw a significant advantage of CJP over the traditional SCRA technique. Differences in primary endpoint, study design, definition of selection criteria and method of diagnosis of AL might explain discrepancies between the present results and those of previous studies.…”
Section: Discussioncontrasting
confidence: 99%
“…It may also have an adverse effect on long‐term bowel function, quality of life, cancer‐specific survival, local recurrence and rate of permanent stoma. Previous studies reported that the incidence of major AL was reduced when CJP reconstruction was performed in patients with a stapled colorectal anastomosis. Another recently described technique of reconstruction is the side‐to‐end colorectal anastomosis, which could potentially have been included in this trial.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another study limitation is the type of anastomosis employed since previous literature has proven that type of anastomosis could be of influence on functional outcome [23, 24]. Patients in the LAR group had a side-to-end anastomosis, while patients in the TaTME group had an end-to-end anastomosis.…”
Section: Discussionmentioning
confidence: 99%
“…The more proximity to anal verge, the more risk of rectal dysfunction. Thus for distal rectal cancer (2-6 Cm from anal verge), it is preferred to save anal canal as possible (Tenckhoff et al, 2015). In our study the proximity to anal verge was 3-8Cm.…”
Section: Discussionmentioning
confidence: 50%